POTENTIAL USE OF BLACK SOLDIER FLY (Hermetia illucens L.) TO INCREASE PEASANTâS INCOME IN INTEGRATED FARMING SYSTEM MODEL - Nursyafitri Amalia, Delita
Rice crop farmers in Indonesia, especially West Java, are still dominated by smallholders peasants and result in the low income of lowland rice farmers. Integrated Farming System (IFS) has the potential to increase revenue for limited land by utilizing the Black Soldier Fly or BSF (Hermetia illucens L.) (Diptera: Stratiomyidae) as biological agents connecting each business component in the SPT. The purpose of this study is to compare the effect of using BSF on commodity productivity, farmer income, efficiency of production costs through calculation of R / C ratio and break even point (BEP), and making IFS models. The use of BSF larvae at 0%, 30%, and 50% of native chicken researched on Completely Randomized Design (CRD) and the use of liquid residues (leachate) BSF as organic fertilizer in rice and large chili with true experiment and posttest testing method only. The use of BSF gave a significant increase in productivity results in rice with productive the number of grains per panicles was 17.36 ± 1.98 and 229.89 ± 18.14, native chickens were fed 50% BSF with an average weight of 861.33 ± 108.51 kg, and large chili with the first day of flowering and harvest result was 35.47 ± 0.90 days and 0.45 ± 0.11 kg, influencing the increase in farmers' income in rice commodities by 363.94%, free-range chicken is 978.27%, and large chili is 116.22%, and influences the increase in R/C by 0.094 in rice, 0.289 in free-range chicken, and 0.231 in chili, and decreases BEP value in rice by 0.025kg or IDR 129.92, in native chickens 10.622kg or IDR 424,864.92, and in large chili 0.004kg or IDR 82.88. The SPT model was designed involving native chickens, rice, and chili as a component of the IFS with BSF as a catalyst agent in processing all three wastes to be able to convert waste into input.